Conhecimentos de astronomia presentes na estrutura dos argumentos de estudantes revelados a partir do trabalho com história problematizadora - Gomide, Hanny Angeles (2012)
This research, based on a qualitative approach, presents and analyzes results about how a group of 26 elementary school students employ knowledge of astronomy in the form of arguments over the implementation of an education proposal, titled History problematizing (HP). To this end, we seek to answer the following question: what knowledge of astronomy that are present in the structure of the argument of the students when they participate in a teaching problem-called history. We work with HP called: A Journey to the luminous shadows, which deals with the shape of the Earth through the study of the shadows. HP relies on assumptions of investigative work, having as one of its features with active involvement of students in the learning process. It consists of a piece of fiction, played by imaginary characters, who leads the student to solve a problem related to the topic. Its solution is sought from group activities, fueled by materials that act as support, providing support for students, to manipulate them, raise hypotheses, socialize them and build their arguments. The didactic sequence addressed in HP includes activities that involve reading of history, interpretation, socialization, relationship with everyday events, problem solving, materials handling, production of written reports and systematization of the results. Students participate in the activity, present their ideas in the form of arguments, which may be similarities with the model proposed by Toulmin, from which we analyzed the data and identify the knowledge of astronomy that have emerged. The data collection instruments were recorded videos of the speeches of the students, the written records and nonverbal indicators, which include attitudes, gestures and actions that students had during the implementation of the proposal. The results revealed that work with HP provided interaction among peers, favored the exposure of students' knowledge about the theme. When analyzed according to the argument structure of Toulmin, have basics such as data, explanations and conclusions. As for the knowledge disseminated, research has shown that students look for ways to find answers to the problem exposed in the story and employ explanatory models that guide in conceptions of the earth flat and static, with the sun revolving around it. These data, and show how students' conceptions are resistant to change, also show the difficulty in addressing the shape of our planet from the study of the shadows. With respect to HP, we realize that students remain stuck to the data of history, seeking to adapt their designs to the one proposed by history or even manipulating materials to corroborate the information brought by it. While working with the story have proved problematical as a possibility of active involvement of learners in the learning process, implications for the future lead us to think that the development of new stories should bring in its plot elements that offer different points of view, encourage further discussion from diverse conceptions.